2009
DOI: 10.1590/s1807-59322009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Anesthesia for Dental Treatment in Cardiac Patients: A Comparative Study of 2% Plain Lidocaine and 2% Lidocaine with Epinephrine (1:100,000)

Abstract: OBJECTIVES: This study analyzes hemodynamic changes in patients with cardiac valvular diseases submitted to dental treatment under local anesthesia containing epinephrine. METHODS: This randomized clinical trial was performed at the Dental Division of the Instituto do Coração do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo (Brazil). Patients were separated into two groups with the help of an aleatory number table: 2% plain lidocaine (PL, n= 31) and 2% lidocaine with epinephrine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
0
29
0
8
Order By: Relevance
“…This could be more closely related to patient anxiety or discomfort, as has already been seen in healthy individuals (14). Likewise, Laragnoit et al (3) reported no increases in heart rate or blood pressure in patients with heart disease during dental treatment with local anesthesia plus a vasoconstrictor. Neves et al (5), in patients with …”
Section: Discussionmentioning
confidence: 98%
“…This could be more closely related to patient anxiety or discomfort, as has already been seen in healthy individuals (14). Likewise, Laragnoit et al (3) reported no increases in heart rate or blood pressure in patients with heart disease during dental treatment with local anesthesia plus a vasoconstrictor. Neves et al (5), in patients with …”
Section: Discussionmentioning
confidence: 98%
“…Chez les sujets coronariens, dans une étude publiée en 1986 chez 40 patients ayant fait un IDM de moins de trois semaines, aucune complication cardiovasculaire grave n'est survenue lors d'extractions dentaires avec un anesthé-sique associé à de l'adrénaline [11]. En 2007, deux essais thérapeutiques, incluant chacun 54 et 62 malades atteints d'une maladie coronarienne, ont évalué l'effet de l'adrénaline en anesthésie locale sur les paramètres hémodynamiques et l'ECG [12,13] ; il n'y avait aucune différence pour la pression artérielle, la fréquence cardiaque, l'ischémie myocardique et l'arythmie cardiaque entre les deux groupes de malades (avec ou sans vasoconstricteur d'effets délétères de l'adrénaline sur les paramètres hémody-namiques et l'ECG [14]. Avec les β-bloquants, aucun cas d'interaction médicamen-teuse néfaste n'a été rapporté en chirurgie buccale [1].…”
Section: Discussionunclassified
“…Patients with cardiovascular disease are at a greater risk of massive endogenous adrenalin release secondary to deficient local anesthesia than of reaction to the small amount of vasoconstrictor used in local anesthetics. 9,10,11,12 Nevertheless, vasoconstrictor use should be limited, taking care not to exceed 0.04 mg of adrenaline. this occurs following thrombus formation secondary to an atheroma plaque that occludes the arterial lumen, though other factors such as cold, physical exercise or stress can act as coadjuvant factors or (less frequently) trigger the event themselves.…”
Section: 4mentioning
confidence: 99%